Risk on design and build for construction project faced by developer / Muhammad Syakirin Ismail - Ismail, Muhammad Syakirin (2003)
As mentioned by Daniel Tan (2000) in his study, Design and Build contracts appears to be a phenomenon trend in Malaysia for developments. It is becoming evident that a significant proportion of both public and private projects are adopting the Design and Build construction procurement route. However, a tremendous growth of Design and Build was limited by some risks and problems. To address this matters, this study consisted of a literature review, a survey to examine knowledge level and perception of developers to risk in Design and Build. Various significant sources and the main contributors of risk that affect the implementation of Design and Build were also studied. Besides that, it also identified stages in construction, which have high extent of risk and main contributors of risk. It was found that most respondents have high knowledge of risk. Five significant sources of risk were identified, these include: Insufficiency of client's brief, inexperience of contractor, changes in requirements, lack of communication, and performance contractor failure. Further more, the construction phase has been identified as a high extent of risk in Design and Build projects, it is also the conclusion of this study that clients appears as a main contributor of risk in Design and Build compared to other parties.